Unified Approach to The Electromagnetic Field: The Role of Sources, Causality and Wave Propagation - Suárez, Álvaro (2023)
The question of the sources of electric and magnetic fields and their causes has been discussed extensively in the literature over the last decades. In this article, we approach this problem from the unified treatment of electromagnetic fields emphasizing the role of their sources in accordance with the cause-effect relationships. First, we analyze whether this unified treatment contributes to a better understanding of these phenomena. Then, we discuss the implications for teaching of a correct understanding of electromagnetic field sources and causality in Maxwell's equations. In particular, we present a series of examples at the introductory physics level that allow us to recognize the reasons why considering electric and magnetic fields as disjoint entities can lead to contradictions.